2019
DOI: 10.1055/a-0897-3966
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma Guidelines and Their Recent Updates: Implications for Imaging

Abstract: Background In 2014, the diagnostic criteria for multiple myeloma were updated, leading to revised recommendations for imaging modalities and definition of therapy response. This review provides an overview of the current definitions of monoclonal plasma cell disease, diagnostic options, and changes relevant to radiologists. Method A pubmed search regarding the multiple myeloma guidelines was conducted, and results were filtered considering publications of international associations and expert revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 50 publications
1
21
0
2
Order By: Relevance
“…The prognostic impact differs even between trisomies; trisomy 21 impairs but trisomy 3 and 5 seem to improve overall survival. Guidelines for skeletal evaluation by imaging are also given [339,340]. Although several studies suggest the analysis of gene expression profiles in malignant plasma cells -37can be used for prognostic subclassification possibly in combination with the Revised-ISS [341][342][343], the guidelines do not recommend the use of this parameter for the diagnosis or monitoring of myeloma patients in routine clinical practice.…”
Section: %mentioning
confidence: 99%
“…The prognostic impact differs even between trisomies; trisomy 21 impairs but trisomy 3 and 5 seem to improve overall survival. Guidelines for skeletal evaluation by imaging are also given [339,340]. Although several studies suggest the analysis of gene expression profiles in malignant plasma cells -37can be used for prognostic subclassification possibly in combination with the Revised-ISS [341][342][343], the guidelines do not recommend the use of this parameter for the diagnosis or monitoring of myeloma patients in routine clinical practice.…”
Section: %mentioning
confidence: 99%
“…It suggested that the adjusted U-Net model had better segmentation effects on the CT image of multiple myeloma. Image processing is an integral part in the detection of lesion area [ 18 ]. The deep learning-based model needs to classify the target areas after the recognition and positioning [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their cross-sectional dimension and the assessment of growth or shrinkage with either technique are two aspects included in the standard IMWG response criteria defining a partial response and a minimal response [ 13 ]. FDG-PET-CT has alternatively become established for the evaluation of extraosseous disease, since it is more sensitive than CT due to the uptake of FDG in these lesions and because it yields morphological, biochemical and functional information [ 18 , 25 , 33 ].…”
Section: Whole-body Computed Tomography (Wbct)mentioning
confidence: 99%